“Gaziel” y El Sol, un proyecto periodístico imposible (diciembre 1934-enero 1935) - Gonzàlez i Vilalta, Arnau (Cuadernos de Historia Contemporánea, 2006)
This article analyses the until now unknown project, that at the end of 1934 could bring the Catalan journalist Agustí Calvet, called “Gaziel”, to the direction of the journal El Sol. Along the years of Second Republic the link between parties and journals was strong. In this context, the letters between “Gaziel” and Ángel Osorio y Gallardo, lawyer, explain the failed purpose to get a journal in which all political tendencies could be expressed. This project could have changed the path of El Sol, that since its origin had an ambiguous trajectory. Those objectives were impossible after October 1934, when the political break-up made impossible any transversal ideological project.